Why Similar Zakat Inputs Produce Divergent Micro-Retail Outcomes: Evidence from BAZNAS Z-Mart in Post-Disaster Palu - Fitrianur; Nur Syamsu; Dede Arseyani; Syaifullah; Nur Wanita (Iqtishodia: Jurnal Ekonomi Syariah, 2026)
This study examines why beneficiaries of the BAZNAS Z-Mart program in post-disaster Palu achieved different micro-retail outcomes despite receiving similar support. Using a qualitative comparative case study of four active beneficiaries, the research integrates the Sustainable Livelihood Framework, Theory of Change, and Maqasid al-Shariah to explain this divergence in vulnerable local recovery settings. Data were collected through in-depth interviews and structured case documentation and analyzed using a hybrid deductive-inductive coding approach. The findings show that outcomes depended less on capital assistance itself than on beneficiaries’ ability to translate support into routine managerial practice. Better outcomes were associated with sound cash flow management, practical business skills, stronger customer and supplier relationships, and effective use of physical business improvements. Poorer outcomes were linked to mixed household and business finances, weak bookkeeping, intense local competition, and psychosocial pressures. Islamic values reinforced positive outcomes when accompanied by operational discipline, contributing to capability, resilience, and the long-term sustainable recovery of livelihoods.